Standarisasi Aliran Proses dan Informasi Pada Departemen Transport di PT A - Aurino, Fendy; Bendatu, Liem Yenny (Jurnal Titra, 2015)
PT A is a manufacturing company which produces consumer goods. Transportation Department wants to standardize the process and information flow by eliminating waste. This research is using Value Steam Mapping (VSM) tool. There are 3 types of waste that are identified in Transportation Department which are overprocessing waste, waiting waste, and defect waste. Improvement suggestion for each waste will impact the next process and hence will reduce the total process time. The result shows the improvement can reduce total lead time by 0,05 % or 56,01 minutes for own truck and 1,10 % or 15,81 hours for trip-based truck distribution everyday.